THE EFFECTIVENESS OF FLASHCARDS IN TEACHING VOCABULARY FOR SEVENTH GRADE STUDENTS OF SMP WAHIDIYAH KEDIRI - LATHIFAH NUR MA'RIFAH; IMAM SUHAIMI (Buana Pendidikan, 2020)
This research is generally to find out the differences in the English vocabulary ability between students are taught by using Flashcards and those are not taught by using Flashcards for seventh grade students of SMP Wahidiyah Kediri. The research applied in Experiment Class and Control Class. The instruments for collecting the data were interview, field note, Pre-test and Post-test. The researcher uses Quasi-experiment and uses quantitative method with analyzed the data by using T-test. The result shows that there is significance different between students are taught by using Flashcards and those are taught by using TPS (Think Pair Share). The data analysis shows that Tcount >Ttable (4,330 > 1,664), Ha is accepted. In Pre-test, the average score of Experiment Class is 62, 44 and Control Class is 72, 79. In Post-test, the average score of Experiment Class is 83, 49 and Control Class is 69. The result shows that the average score of Experiment Class is higher than Control Class in Post-test.